Terperangkap Kultur Patriarki: Kegagalan Penerapan Prinsip Cedaw Terhadap Kasus Honour Killing Di Pakistan - Handoyo, Khalda Khairunnisa; Rosyidin, Mohamad (Journal of International Relations, 2020)
Pakistan is one of the 189 countries that had been ratified Convention on the Elimination of All Forms of Descrimination Against Woman (CEDAW), a convention that protects women rights. However the practice of honour killing still occured on women in Pakistan. This paper will provide an explanation on why there is still an honour killing practice even though Pakistan had been ratified CEDAW. This paper will use constructivism theory to analyze this problem, more specifically using cultural concept. It is based on the author argument that seeing the main reason the occurance of honour killing is not because mere legal factors. The autor emphasize that the patriarchial culture is the main reason why honour killing continue to occur until now.